Tinjauan Tafsir Maqasidi terhadap Kisah Nabi Zakaria: Analisis Qs. Maryam [19]: 1-11 - Lia Nikmatul Maula; Sri Kurniati Yuzar (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This article aims to explain the story of the prophet Zakaria by using the review of maqasidi interpretation. The story of prophet Zakaria is one of the many stories of the prophets in the Qur'an that emphasizes the aspect of Tawhid. In the Qur'an, it is explained that Prophet Zakaria was a prophet who always prayed to Allah SWT to be blessed with a child even though he was old and his wife was barren. Because of his seriousness in praying, Allah SWT granted the prayer by giving good news in the form of his wife's pregnancy. Allah told him that his wife would give birth to a son named Yahya who would continue his prophetic treatise. This research is a librarry research using maqasidi interpretation approach. The results of this study indicate that when reviewed using the perspective of maqasidi interpretation in QS. Maryam (19): 1-11, Zakaria's determination in praying is a manifestation of his strong obedience to Allah. This contains maqasid, namely as a form of guarding religion (hifz al-Din). While the fulfillment of the prayer of the prophet Zakaria in the form of being given a child is a form of guarding by Allah SWT against offspring, as a form of maintaining prophetic regeneration. This contains maqasid, namely the preservation of offspring (hifz al-Nasl). The importance of preserving religion (hifz al-Din) and preserving offspring (hifz al-Nasl) is the goal of Islamic law that must be fulfilled.